Ketahanan diri akademik dalam kalangan murid daripada ibu bapa bercerai [Academic resilience among student from divorced parents] - Kasim, Marini; Ahmad, Nor Shafrin (Universiti Utara Malaysia Press)
Objectives – This study was conducted to determine the influence of the protective factor and internal strength on academic resilience among students of divorced parents. The study also aims to identify the dimensions of protective factors and internal strengths that become the predictors of student’s academic resilience of divorced parents. Methodology – Mixed methods approach of quantitative and qualitative methods were administrated through questionnaires and interviews with form four students from selected schools in Kedah. The respondents for quantitative methods consist of 46 form four students who have been selected through systematic sampling from 19 schools in Kedah. As for the qualitative method, 5 pupils were selected using purposive sampling. The interview questions were designed to further study the role, the influence of protective factors and internal strength in improving students’ academic resilience who are from the divorced parents. The triangulation method is used to see the equivalence between quantitative and qualitative data so that the findings are more comprehensive. Findings – Overall the findings demonstrate that the variables of protective factors, internal strength and resilience is at a high level. The interview results show that the protective factors play a greater role in improving academic resilience than internal strength. All respondents found close relationships and appreciates the close relationship between siblings, friends or teachers at school. Significant – The findings indicate that there is a critical need especially for teachers to understand the protective factors that can enhance the focus of the students during the teaching and learning process as well as the students’ overall resilience in the academic field. The combined quantitative and qualitative findings have provided information that teachers can use as a guideline in identifying the initial steps that need to be taken to address students’ readiness to learn in the event of divorce.